Influence of intranasal and carotid cooling on cerebral temperature balance and oxygenation - Nybo, Lars; Wanscher, Michael; Secher, Niels H. (Frontiers in Physiology, 2014)
The present study evaluated the influence of intranasal cooling with balloon catheters, increased nasal ventilation, or percutaneous cooling of the carotid arteries on cerebral temperature balance and oxygenation in six healthy male subjects. Aortic arch and internal jugular venous blood temperatures were measured to assess the cerebral heat balance and corresponding paired blood samples were obtained to evaluate cerebral metabolism and oxygenation at rest, following 60 min of intranasal cooling, 5 min of nasal ventilation, and 15 min with carotid cooling. Intranasal cooling induced a parallel drop in jugular venous and arterial blood temperatures by 0.30 ± 0.08 ºC (mean ± SD), whereas nasal ventilation and carotid cooling failed to lower the jugular venous blood temperature. The magnitude of the arterio-venous temperature difference across the brain remained unchanged at - 0.33 ± 0.05 ºC following intranasal and carotid cooling, but increased to - 0.44 ± 0.11 ºC (P< 0.05) following nasal ventilation. Calculated cerebral capillary oxygen tension was 43 ± 3 mmHg at rest and remained unchanged during intranasal and carotid cooling, but decreased to 38 ± 2 mmHg (P< 0.05) following increased nasal ventilation. In conclusion, percutaneous cooling of the carotid arteries and intranasal cooling with balloon catheters are insufficient to influence cerebral oxygenation in normothermic subjects as the cooling rate is only 0.3 ºC per hour and neither intranasal nor carotid cooling is capable of inducing selective brain cooling.